2020
DOI: 10.3390/cells9092003
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs Associated with Dysregulated Vascular and Trophoblast Function as Target-Based Diagnostic Biomarkers for Preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy-specific disorder associated with hypertension and proteinuria. Since there is no proven method to treat PE, early prediction and accurate diagnosis are essential for appropriate management of the disease. Thus, reliable biomarkers for diagnosing PE need to be identified and evaluated. We analyzed serum-soluble factors and miRNAs in 92 patients with PE and an equal number of healthy controls to identify new useful biomarkers for PE. Serum miR-31-5p, miR-155-5p, and miR-214-3p l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
1
31
1
Order By: Relevance
“…Thus, the three isoforms of NOS, including iNOS, nNOS and eNOS, are all produced by first trimester trophoblast cells. In addition, we discovered that the expression of all the three NOS isoforms, including iNOS, was suppressed by hydrogen peroxide incubation in TEV-1 cells, which is not consistent with a previous report showing that the serum iNOS levels were increased in PE patients ( Kim et al, 2020 ). We hypothesis that the inconsistence could be due to the complicated cellular pathways functioning during PE progression in patients, since iNOS expression is also regulated by other molecules such as Tumor Necrosis Factor-α (TNF-α) that is stimulated in PE ( Kim et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 91%
“…Thus, the three isoforms of NOS, including iNOS, nNOS and eNOS, are all produced by first trimester trophoblast cells. In addition, we discovered that the expression of all the three NOS isoforms, including iNOS, was suppressed by hydrogen peroxide incubation in TEV-1 cells, which is not consistent with a previous report showing that the serum iNOS levels were increased in PE patients ( Kim et al, 2020 ). We hypothesis that the inconsistence could be due to the complicated cellular pathways functioning during PE progression in patients, since iNOS expression is also regulated by other molecules such as Tumor Necrosis Factor-α (TNF-α) that is stimulated in PE ( Kim et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 91%
“…Unlike previous studies [23, 26], in this study, we applied the case-control study and longitudinal study, in which the subjects from both studies were independent. Through the case-control study with a large sample size, we observed that about 30% preeclamptic patients presented high sero-miR-155 level and through longitudinal study we not only found the similar proportion of preeclamptic patients with high sero-miR-155 but also observed that the increase of miR-155 level took place as early as at GW11-13 +6 and maintaining high level across pregnancy, suggesting that certain proportion of preeclamptic patients with high sero-miR-155 level indeed existed and miR-155 was not fit for an uniform predictor for preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the uterus and the embryo is vital for the successful implantation and development of the embryo during pregnancy. Endometrial tissue biopsy in cows before implantation of embryos at days 3 and 7 of the estrous cycle (similar to the human menstrual cycle) showed that the expression of several miRNAs changed during this period so that the expression of miR-1290 increased up to 10-fold on day 7 of the estrous cycle under normal conditions [49]. Therefore, more studies are needed on human samples to determine whether the expression of miR-1290 is important for embryo implantation and normal pregnancy.…”
Section: The Imaginable Function Of Mir-1290 As a Novel Diagnostic Bi...mentioning
confidence: 94%